Biodiversity and DNA Barcoding of Seagrass in an Equatorial Small Island Ecosystem of Kayoa Island, Eastern Indonesia - Riyadi Subur; Nebuchadnezzar Akbar; Salim Abubakar; Firdaut Ismail; Rustam E Paembonan; Beginer Subhan; Dondy Arafat; Muhammad Irfan (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract Highlight Research 1. This research provides initial and current information regarding seagrass on small islands right on the equator. 2. directly depicts the diversity, density and cover of seagrass in a unique region, namely a small island crossed by the equator. 3. The environmental conditions of marine waters in seagrass areas on islands crossed by the equator have been described. 4. The latest information specifically describing seagrass and the ecology of equatorial marine environments. Essential for the development of future knowledge and technology. 5. DNA barcoding was capable of resolving field identification challenges and providing taxonomic clarification based on DNA sequence data.   Abstract Equatorial small islands host dynamic coastal ecosystems, yet seagrass biodiversity and molecular identification remain poorly documented. Complete information on coastal ecosystems has not been provided for seagrass in the equatorial latitudes. Seagrass is dynamically distributed throughout the equatorial latitudes. The area that the equatorial latitudes also traverse is known as the indotropic region. Eastern Indonesia’s Kayoa Island is situated directly on the equator. However, seagrass biodiversity and DNA-based species confirmation in this region remain insufficiently documented. There are no published research on seagrass, particularly on biodiversity. The aim of this study is to reveal the diversity of seagrass in equatorial latitudes on the small islands. The methodology in this study was purposive sampling with a quadrant line transect was used to obtain the samples. In situ identification of seagrass species was done. Seagrass samples were taken from the leaves for DNA analysis purposes. Leaf samples were analyzed using molecular methods in the laboratory. To determine the distribution of seagrass ecology and environmental were subjected to PCA analysis. The results showed that six seagrass species were identified. It has been discovered that seagrass may develop in the tropical region under typical environmental conditions. Despite the fact that six species were discovered, diversity was limited. In this region, seagrass cover is typically high and supports a healthy species density. Species diversity was low, whereas percent cover and density were locally high. Overall, the study indicated relatively low diversity and density values. DNA barcoding has revealed differences in morphological identification.This discovery represents preliminary data that can be investigated further in subsequent studies.